Harlequin Ichthyosis: Navigating the Challenges of a Rare Case (GAIMS Journal of Medical Sciences, 2024)
Ichthyosis, derived from the Greek word "ichthys" meaning fish, encompasses various skin disorders characterized by dry, scaly, and thickened skin, often inherited through autosomal or X-linked modes. This case report discusses a rare and severe form known as Harlequin ichthyosis, presenting a second gravida woman with consanguinity history who delivered a male baby with characteristic features including porcelain-like skin, ectropion, eclabion, and flexion deformities. Despite supportive measures, the baby died shortly after birth. Harlequin ichthyosis, with an incidence of 1 in 300,000 births, arises from mutations in the ABCA12 gene, affecting lipid exocytosis and desquamation. Antenatal diagnosis is feasible through ultrasound findings and genetic testing, with a grim prognosis and limited survival beyond infancy. This report underscores the challenges in managing such conditions and highlights the importance of ongoing research for better understanding and management.